Efforts To Increase Motivation For Learning Science Through Experimental Methods In Class V Students - Rohyani, Untung (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this research is to increase students' learning motivation in science subjects in grade V elementary schools using experimental methods. The research carried out was Class Action Research (PTK) in two cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, action, observation and reflection. At each meeting, observations and questionnaire tests were held to determine changes in students after giving action in cycle 1 and cycle 2. The results of research using experimental methods were proven to increase the science learning motivation of class V students at SD Negeri 1 Sajen, Trucuk. The increase can be seen in the average student learning motivation score from the initial state of 47.28, increasing in cycle I, namely 54.49, then increasing in cycle II to 65.49. These results show that the experimental method can increase students' learning motivation, especially the Class V science subject at SDN 1 Sajen.